The stock exchange of Singapore : a price-volume analysis - Eik, Wai Kay (2014)
This study aims to examine the relationship between price changes and volume of stocks listed on the Stock Exchange of Singapore (SES). The two main relationships to be proven in this study are the relationship between price change and volume; and the relationship between price change and volume change. Using daily share prices of the top 29 stocks according to market capitalisation values, from 1 January 1992. to 31 December 1994, the results of this study suggested that: (1) There is a positive relationship between absolute price changes and trading volume; (2) A positive relationship is obtained between absolute price changes and changes in trading volume; (3) Trading volume is greater for upticks than for price downticks for a given absolute magnitude of price change; (4) There is no significant relationship between trading volume and the serial correlation of stock returns; (5) No significant relationship exists between changes in trading volume and the serial correlation of stock returns. On the whole, the results in this study are generally consistent with the empirical findings conducted in other developing equity markets, with the exception of the relationship between volume and serial correlation of returns.